Study of infective morbidity following gynecological surgeries - Gavhane, Satyajit P.; Bangal, Vidyadhar B.; Gagare, Swati D.; Kodlikeri, Amey R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Post-operative wound infection is a common nosocomial infection all over the world. It is responsible for increase in physical and psychological stress to the patient. It also increases the cost of treatment due to prolonged hospitalization. Present study was carried to find out the post-operative wound infection, morbidity and the risk factors. Methods: Prospective cross sectional study was carried out at tertiary care teaching hospital for a period of six months. Consecutive 57 cases of surgical site infections (SSI) following obstetric and gynecological abdominal surgery were analyzed. Results: It was observed that the incidence of SSI was 2.8 percent. Overweight, previous laparotomy scars, emergency surgery and prolong labour were the common risk factors associated with the development of SSI. Certain epidemiological and environmental factors like under nutrition, rural area residence, poverty, illiteracy, ignorance, poor general hygiene, Surgical site infections(SSI) were more commonly observed following emergency operations; laparotomies performed for large ovarian tumours, malignancies and ruptured ectopic pregnancies. Caesarean sections performed for prolong labour, prolong premature rupture membranes, prolonged second stage had more likelihood of development of sepsis. Occurrence of SSI resulted in significant prolongation of hospital stay. Conclusions: The incidence of SSI in the present study was within acceptable limits. Regular surveillance for SSI in the hospital and sensitization of staff regarding consequences of SSI would go a long way in further reduction in the rate of SSI.